Fire retardancy of polymeric materials - Wilkie, Charles A., 1941-; Morgan, Alexander B. (CRC Press, 2010)
When dealing with challenges such as providing fire protection while considering cost, mechanical and thermal performance and simultaneously addressing increasing regulations that deal with composition of matter and life cycle issues, there are no quick, one-size-fits-all answers. Packed with comprehensive coverage, scientific approach, step-by-step directions, and a distillation of technical knowledge, the first edition of Fire Retardancy of Polymeric Materials broke new ground. It supplied a one-stop resource for the development of new fire safe materials. The editors have expanded the second edition to echo the multidisciplinary approach inherent in current flame retardancy technology and put it in a revised, more user-friendly format. More than just an update of previously covered topics, this edition discusses: additional fire retardant chemistry developments in regulations and standards new flame retardant approaches fire safety engineering modeling and fire growth phenomena The book introduces flame retardants polymer-by-polymer, supplemented by a brief overview of mode of action and interaction, and all the other ancillary issues involved in this applied field of materials science. The book delineates what, why, and how to do it, covering the fundamentals of polymer burning/combustion and how to apply these systems and chemistries to specific materials classes. It also provides suggested formulations, discusses why certain materials are preferred for particular uses or applications, and offers a starting point from which to develop fire-safe materials.